Five Hidden Species in a Widespread European Vertebrate: Disentangling the Alpine Newt Cryptic Species Complex Through Genomic Phylogeography - Stephanie Koster; Anagnostis Theodoropoulos; Wouter Beukema; Johanna Ambu; Wiesław Babik; Daniele Canestrelli; Andrea Chiocchio; Dan Cogălniceanu; Milena Cvijanović; Manon C. de Visser; Christophe Dufresnes; James France; et al. (Molecular Ecology, 2026)
Through genomic phylogeography, previously unrecognised biodiversity can be revealed. The alpine newt serves as a case in point: this taxon carries highly distinct mtDNA clades and has a severely fragmented range. We obtain genome‐wide data with target enrichment by sequence capture to delineate cryptic species and disentangle their phylogenetic relationships. Furthermore, we explore potential niche divergence and glaciation‐driven distribution dynamics. On the basis of the uncovered genetic structure, we distinguish five main groups that we propose should be treated as distinct species. Limited interspecific genetic admixture often occurs away from current contact zones between these species, in line with a scenario of current range reduction, compared to the Last Glacial Maximum. A decline in suitable habitat also explains the fragmented nature of current species ranges. We uncover pronounced mito‐nuclear discordance. We show that an ancient mtDNA lineage endemic to the Vlasina Plateau on the border between Serbia and Bulgaria, previously interpreted to be a ‘ghost lineage’, in fact represents a distinct species. However, it is nested considerably deeper inside the alpine newt species complex than mtDNA suggests. Our study illustrates how genomic phylogeography allows intricate evolutionary histories to be untangled.

The Dry‐Climate Hypothesis: Identifying the Environmental Drivers of Terrestrial Viviparous Salamanders - Marco Dinis; Fernando Martínez‐Freiría; Wouter Beukema; Sergé Bogaerts; Guillermo Velo‐Antón (Journal of Biogeography, 2025)
Aim The evolution of adaptive innovations carries strong eco‐evolutionary implications, allowing organisms to explore novel ecological opportunities, which facilitates lineage diversification. The remarkable diversity of reproductive strategies in amphibians provides a natural laboratory for identifying ecological mechanisms driving evolutionary novelties. In viviparous salamanders, the transition from larviparous (i.e., live bearing of aquatic larvae) to pueriparous (i.e., live bearing of fully terrestrial juveniles) reproduction is hypothesized to represent an adaptation to the absence of water for larval deposition, in what is known as the dry‐climate hypothesis. This work aimed to identify the ecological drivers of independent evolutionary transitions to pueriparity and test the dry‐climate hypothesis. Location Western Palearctic. Taxon Salamanders of the Salamandra and Lyciasalamandra genera. Methods A comparative ecological niche‐based framework spanning the entire known distribution of larviparity and pueriparity in salamanders was used to identify the ecological drivers of this reproductive transition. Niche divergence was tested between (a) viviparous modes and (b) independent origins of pueriparity to assess the existence of ecological differentiation between groups. The relative contribution of environmental factors to niche divergence was assessed by regression analysis. Results We found that independent transitions from larviparity to pueriparity are consistently associated with ecological differentiation driven primarily by steep topography and karstic geology. Main Conclusions Reproductive transitions to pueriparity in salamanders were consistently associated with scarcity of surface water driven by steep topography and karstic geology, providing the most unambiguous support for the dry‐climate hypothesis to date and supporting convergent evolution of terrestrialisation in salamanders for most pueriparous lineages. Climatic, hydrological (i.e., soil moisture and vapour pressure deficit) and habitat factors appear to be comparatively less relevant drivers of reproductive shifts, yet may have played a role in specific transitions to pueriparity, especially at the intraspecific level. We also found key differences in the use of available habitat between reproductive modes, with pueriparity representing a more specialised strategy likely restricted to areas with strong selective pressure against aquatic breeding.

Microclimate limits thermal behaviour favourable to disease control in a nocturnal amphibian - Wouter Beukema; Frank Pasmans; Sarah Van Praet; Francisco Ferri‐Yáñez; Moira Kelly; Alexandra E. Laking; Jesse Erens; Jeroen Speybroeck; Kris Verheyen; Luc Lens; An Martel (Ecology Letters, 2021)
While epizootics increasingly affect wildlife, it remains poorly understood how the environment shapes most host–pathogen systems. Here, we employ a three‐step framework to study microclimate influence on ectotherm host thermal behaviour, focusing on amphibian chytridiomycosis in fire salamanders ( Salamandra salamandra ) infected with the fungal pathogen Batrachochytrium salamandrivorans ( Bsal ). Laboratory trials reveal that innate variation in thermal preference, rather than behavioural fever, can inhibit infection and facilitate salamander recovery under humidity‐saturated conditions. Yet, a 3‐year field study and a mesocosm experiment close to the invasive Bsal range show that microclimate constraints suppress host thermal behaviour favourable to disease control. A final mechanistic model, that estimates range‐wide, year‐round host body temperature relative to microclimate, suggests that these constraints are rule rather than exception. Our results demonstrate how innate host defences against epizootics may remain constrained in the wild, which predisposes to range‐wide disease outbreaks and population declines.

Area prioritization and performance evaluation of the conservation area network for the Moroccan herpetofauna: a preliminary assessment - Philip de Pous; Wouter Beukema; Martijn Weterings; Ignas Dümmer; Philippe Geniez (Biodiversity and Conservation, 2011)